Kidney injury is independent of endothelial HIF-1? - Kalucka, Joanna; Schley, Gunnar; Georgescu, Adela; Klanke, Bernd; Roessler, Susanne; Baumgartl, Jasmin; Velden, Joachim; Amann, Kerstin Ute; Willam, Carsten; Johnson, Randall S.; Eckardt, Kai-Uwe; Weidemann, Alexander (Journal of Molecular Medicine, 2015)
Hypoxia-inducible transcription factors (HIFs) control cellular adaptation to low oxygen. In the kidney, activation of HIF is beneficial during injury; however, the specific contribution of HIF-1? in renal endothelial cells (EC) remains elusive. Since EC display tissue-specific heterogeneity, we investigated how HIF-1? affects key functions of glomerular EC in vitro and its contribution to renal development and pathophysiological adaptation to acute or chronic renal injury in vivo. Loss of HIF-1? in glomerular EC induces hypoxic cell death and reduces hypoxic adhesion of macrophages in vitro. In vivo, HIF-1? expression in EC in mouse kidneys is detectable but limited. Accordingly, EC-specific ablation of HIF-1? does not lead to developmental or phenotypical abnormalities in the kidney. Renal function and expression of adhesion molecules during acute ischemic kidney injury is independent of HIF-1? in EC. Likewise, inflammation and development of fibrosis after unilateral ureteric obstruction is not influenced by endothelial HIF-1?. Taken together, although HIF-1? exerts effects on glomerular EC in vitro, endothelial HIF-1? does not influence renal development and pathophysiological adaptation to kidney injury in vivo. This implies a profound difference of the hypoxic response of the renal vascular bed compared to other organs, such as the heart. This has implications for the development of pharmacological strategies targeting the endothelial hypoxic response pathways.HIF-1? controls hypoxic survival and adhesion on endothelial cells (EC) in vitro. In vivo, HIF-1? expression in renal EC is low. Deletion of HIF-1? in EC does not affect kidney development and function in mice. Renal function after acute and chronic kidney injury is independent of HIF-1? in EC. Data suggest organ-specific regulation of HIF-1? function in EC.
EVALuna2:3772